The gut–bone axis in osteoporosis: a multifaceted interaction with implications for bone health - Gu, Chunli; Du, Hong; Li, Ningying; Zhou, Yunlong; Li, Sha; Sun, Yuchen; Han, Yiyang; Xu, Xuan; Li, Xianrong (Frontiers in Endocrinology, 2025)
With the accelerated aging of the population, degenerative orthopedic diseases, particularly osteoporosis, have become a major public health challenge, threatening bone health and affecting the quality of life. Existing anti-osteoporosis regimens remain rather unitary or poorly adhered, which also limits the maintenance of bone health to some extent. Given the increasingly elucidated prominence of gut-related factors in osteoblasts/osteoclasts and bone formation/metabolism/maintenance, focusing on intestinal microecology and then targeting the distal bone tissue via the gut–bone axis have been recognized as a feasible intervention strategy. This review systematically summarized the interaction of the gut–bone axis while highlighting the physicochemical barriers formed by intestinal intrinsic structures, the gut microbiota, and related molecules for bone health maintenance through the immune and endocrine pathways. Meanwhile, we emphasized the ideal anti-osteoporotic property and individual achievability of methods like fecal microbiota transplantation, probiotic and prebiotic supplementation, and dietary pattern modification. The conceptual framework of the gut–bone axis plus X was innovatively proposed, given the potential synergy among different organs in disease characterization and pathogenesis, which may help better explain the etiology and manage other co-morbidities concurrent with or secondary to osteoporosis. Since the intersection of orthopedics with other subjects, we also supported the application of nano-biomaterials, bacterial synthetic biology, and novel small molecules in anti-osteoporosis, which is expected to unlock broader prospects for the multidisciplinary integration of the gut–bone axis.